Assessment of climate change impact on groundwater resources in Hau Giang Province, Vietnam - Hoang Thi Ngoc Anh; Shrestha, Sangam; Babel, Mukand Singh; Andriyas, Sanyogita; Pandey, Vishnu P.; Greater Mekong Subregion (GMS) Scholarship (Pathum Thani, Thailand : Asian Institute of Technology, 2016)
With excellent quality and relatively low development cost, groundwater has been a precious source of water supply in all over the world. It provides water for domestic, irrigation and industrial purposes. In Mekong Delta Vietnam, groundwater is irreplaceable, where other fresh water sources are seasonally lacking. However, climate change, sea level rise and overdraft are now causing adverse impacts, leading to the serious scarcity of groundwater resources. Therefore, this study aims to assess the climate change impact on groundwater in Hau Giang province which will help to improve the understanding of how groundwater responds to climate change. Besides, for the management policy and development plans, this study has quantified the impact of future abstraction scenarios and projected climate change scenarios on groundwater resources.First, the future change in climate in Hau Giang province was generated using General Circulation Model (GCM)data and downscaling technique, which provide the temporal and spatial change in precipitation, and temperature under RCP4.5 and RCP8.5 for the period of 2030s, 2040s and 2050s. By the middle of 21st century, average rainfall is expected to increase by about 1.2% to 2.22% under RCP4.5 and RCP8.5 respectively, and the upward trend of temperature are predicted, raising from 0.59-1.05oC on average. Then the climate scenarios were used as input for WETSPASS model for analyzing the variation in recharge. Future projected recharge data was used in MODEFLOW to analyze and predict the impact of climate change on groundwater. Change in climate conditions in the future result in depletion of groundwater level in Hau Giang province. This study found that the groundwater recharge will change seasonally, varying at different degree. In the dry season, groundwater recharge is predicted to decrease up to 10% corresponding to RCP4.5 scenario and 18% under RCP8.5. Similar to the rainfall in rainy season, the groundwater recharge is projected to rise by 14% and 21% corresponding to RCP4.5 and RCP8.5.The increase of groundwater recharge slow down the depletion rate of aquifers in Hau Giang province. In the past, the groundwater level has continuously decreased from 2.08m to 4.16 m at aquifer qp3, and decline from 1.35m to 3.72m at aquifer qp2-3with an average rate of 0.312m/year and 0.254m/year respectively. From the period from 2020 the groundwater level is projected to decrease with a rate of 0.05m/year at aquifer qp3and 0.1m/year at aquifer qp2-3.It was found that the influence from abstraction scenarios is more severe than climate change scenarios resulting in the depletion of groundwater level and the extension of area covered by the deep piezometric contours (such as -7.5m, -8.0m). At aquifer qp2-3, the minimum groundwater of the abstraction scenario 2050 is deeper than RCP8.5 2050s (in dry season) scenarios by -1.7m.Onaverage, the future abstraction scenarios lead to more depletion of groundwater by -1.5m at four upper aquifers comparing to the future climate scenarios. Comparison of the impact of climate change and future abstraction scenarios would allow the decision makers and other stakeholders for making technical guidelines to set up the limit for groundwater abstraction or promote the aquifer for abstraction
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Water Engineering and Management
Thesis (M. Eng.) - Asian Institute of Technology, 2016
Keywords: Climatic change -- Vietnam -- Hau Giang; Groundwater -- Vietnam -- Hau Giang